1997
DOI: 10.1108/01425459710170086
|View full text |Cite
|
Sign up to set email alerts
|

Islamic revival in Asia and human resource management

Abstract: IntroductionThe last three decades or so have seen a lively debate among both academics and practitioners on the role of national culture in the shape and operation of business organizations. Some authors have emphasized the universality and similarities between organizations (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
1
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(120 citation statements)
references
References 17 publications
1
114
1
4
Order By: Relevance
“…Before describing the expected relationships between cultural orientations and HRM practices, we first present our hypotheses pertaining to the cultural orientations held by Omani employees. Tayeb (1997) aptly observed that "Religions in many countries, with either secular or religious constitutions, have a certain degree of influence on the cultural characteristics of their people and their institutions " (1997: 354). This is especially valid for Islam.…”
Section: Insert Table 1 About Herementioning
confidence: 99%
“…Before describing the expected relationships between cultural orientations and HRM practices, we first present our hypotheses pertaining to the cultural orientations held by Omani employees. Tayeb (1997) aptly observed that "Religions in many countries, with either secular or religious constitutions, have a certain degree of influence on the cultural characteristics of their people and their institutions " (1997: 354). This is especially valid for Islam.…”
Section: Insert Table 1 About Herementioning
confidence: 99%
“…Islamic Work Ethics has its own perspective regarding work-related behaviour as the concept itself is origin in the Quran and the teaching of the Prophet SAW (Saeed Hameed Aldulaimi, 2016). It is argued to be different from Protestant Work Ethics (Ali & Al-Owaihan 2008;Rice 1999) because it emphasises a balanced life (Abu-Tapanjeh 2009), the benefits of mankind (Ali 1988), and anticipating work as an ibadah (Muhammad et al, 2008) or obligation to God (Tayeb 1997). For example, Islam emphasises knowledge sharing behaviour and dislikes those who do not share their knowledge.…”
Section: Problem Statementmentioning
confidence: 99%
“…Moreover, the government has to make sure its religious departments and officers are well-versed in the principles of Islam Hadhari. Tayeb (1997) mentions that Islam is an all-encompassing creed, governing every aspect of life, public and private, political and economic, and as such is relevant to business activities. The Quran advocates a system based on individual enterprise and individual reward.…”
Section: Islam Hadhari's Principlesmentioning
confidence: 99%
“…Furthermore, the studies conducted on the impact of Islam on human resource management (HRM) matters are very few (Tayeb, 1997). Therefore, the study aims to fill the gap, by investigating four principles of Islam Hadhari in relation to reward systems in the Malaysian context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation